Air-Conditioning Unit Harvesting Energy Using DC Generator - Shah Slamet, Mohammad Firman; Zambri, Nor Aira; Salim, Norhafiz (Progress in Engineering Application and Technology, 2020)
The usage of air-conditioning unit in the residential building has increased rapidly in the recent decades. There are waste energies that released from the operation of air-conditioning unit. The main objectives of this paper are to investigate the potential energy from the air-conditioning system, create methods for energy harvest from waste energy and to verify its performance and effectiveness. The scopes will focus on designing a suitable energy harvester on the 1 HP air- conditioner using DC generator. The result presented consist of the DC generator output and it shows that DC generator is able to generate voltage during the starting of the air-conditioning unit operation. This project will help in bringing a new concept of power generation using waste energy.